2023
DOI: 10.1093/humupd/dmad006
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of semen to early embryo development: fertilization and beyond

Abstract: BACKGROUND It has long been thought that the factors affecting embryo and foetal development were exclusively maternally derived; hence, if issues regarding fertility and embryo development were to arise, the blame has traditionally been placed solely on the mother. An escalating interest in how paternal factors influence embryo development, however, has begun to prove otherwise. Evidence suggests that both seminal plasma (SP) and sperm contribute multiple factors that shape embryogenesis. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 449 publications
1
11
0
Order By: Relevance
“…Previous observations from our laboratory showed that females mated with males with mutations in Crisp1 and Crisp3 genes (C1/C3 DKO) exhibited normal in vivo fertilization rates but significantly lower percentages of embryo development, supporting the notion that male-derived factors are required to allow for correct development of the embryo (Vallet-Buisan et al ., 2023). Moreover, we observed that triple knockouts lacking CRISP1, CRISP2 and CRISP3 as well quadruple knockouts lacking the four members of the family exhibited both fertilization and embryo development defects, supporting the lack of CRISP1 and CRISP3 as relevant for the embryo development phenotype.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Previous observations from our laboratory showed that females mated with males with mutations in Crisp1 and Crisp3 genes (C1/C3 DKO) exhibited normal in vivo fertilization rates but significantly lower percentages of embryo development, supporting the notion that male-derived factors are required to allow for correct development of the embryo (Vallet-Buisan et al ., 2023). Moreover, we observed that triple knockouts lacking CRISP1, CRISP2 and CRISP3 as well quadruple knockouts lacking the four members of the family exhibited both fertilization and embryo development defects, supporting the lack of CRISP1 and CRISP3 as relevant for the embryo development phenotype.…”
Section: Discussionsupporting
confidence: 67%
“…Considering various reports showing that male accessory glands contribute to proper embryo development without affecting fertilization rates (Jodar, 2019; Ma et al ., 2022; Vallet-Buisan et al ., 2023; W. S. et al .,1988), the possibility existed that the sperm defects leading to the embryo development phenotype were associated with the lack of CRISP1 and CRISP3 in the accessory gland secretions.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, accumulating evidence suggests that contributions from male-derived factors extend well beyond the provision of the male haploid genome to the early embryo, and semen may play a pivotal role in the intricacies of embryogenesis. 30 In conclusion, despite the potential diminishment of the predictive signi cance of sperm parameters on embryo quality due to the application of semen optimization processes, our data still indicated that sperm DFI could exhibit some predictive power for the fertilization rate during ART cycles. Furthermore, a threshold value of 21.15% has been identi ed, offering potential predictive utility for high fertilization rates (≥ 80%).…”
Section: Discussionmentioning
confidence: 66%
“…In this regard, sperm DNA fragmentation (SDF) is used most in human clinics and breeding centers [7,8]. However, SDF is only one of many levels in sperm chromatin evaluation, and solely focusing on it ignores the complex structural, epigenetic, and other molecular features affecting sperm fertility, embryo development, and even the health and well-being of the offspring [9,10].…”
Section: Introductionmentioning
confidence: 99%